Analisis Intesi Muzakki dalam Membayar Zakat Profesi Kota Medan - Khairul Abdi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the intentions of muzaki in paying professional zakat in Medan City. The research explores various factors influencing muzaki's intentions, including awareness of professional zakat obligations, understanding of zakat concepts, religious beliefs, as well as the influence of the social environment and the role of zakat institutions in encouraging compliance. Data were collected through a survey of muzaki in Medan City and analyzed using a quantitative approach with multiple linear regression methods. The results indicate that high awareness and understanding of professional zakat, social support, and trust in zakat institutions significantly influence muzaki's intention to pay professional zakat. Furthermore, the study finds that the active role of zakat institutions in education and outreach positively impacts the compliance of muzaki. These findings have important implications for the development of more effective zakat policy strategies and for strengthening the role of zakat institutions in enhancing compliance with professional zakat in society.